Hubungan Persepsi Siswa terhadap Penggunaan Media Pembelajaran Wordwall dengan Motivasi Belajar Siswa Kelas IV pada Materi Bangun Datar di SD 229 Paria - Muh. Syahrul Ramadhani; Khaerul Fahmi; Nurannisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the relationship between students' perception of the use of Wordwall learning media and the learning motivation of grade IV students on flat building materials at SD 229 Paria. This study uses a quantitative approach with a type of correlational research. The research population was 19 grade IV students with sampling techniques using total sampling. Data collection was carried out using a closed questionnaire with a Likert scale of 1–4 to measure students' perception of the use of Wordwall and students' learning motivation. The research instrument was validated through expert judgment and tested for reliability using Cronbach's Alpha. Data analysis was carried out using the JASP application through descriptive statistical analysis, Shapiro–Wilk normality test, and Pearson Product Moment correlation test. The results showed that the data was normally distributed with a significance value of 0.849 (p > 0.05). The results of the Pearson correlation test showed a correlation coefficient value of r = 0.791 with a significance value of p < 0.001. These results show that there is a strong and significant positive relationship between students' perception of the use of Wordwall learning media and student learning motivation. Thus, Wordwall learning media can be used as an interactive digital learning media to increase the motivation to learn mathematics for elementary school students, especially in flat building materials.